Knowledge, Perception and Factors Influencing the Risk of Cervical Cancer among Lead City University Female Students in Ibadan, Oyo State (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Introduction: Cervical carcinoma is a significant global health concern, especially in developing nations, where it ranks as the second most common cancer after breast cancer. Despite its prevalence, early detection through screening remains pivotal in curbing its impact. This study focuses on the awareness and perceptions of cervical cancer among female students at Lead-city University, Ibadan, highlighting the need for targeted interventions, especially among high-risk groups.Methods: A descriptive cross-sectional study was conducted among female students residing in the hostels of Lead City University, Ibadan. A multistage sampling technique was employed, involving the systematic selection of rooms and occupants for surveys. Data were collected using a semi-structured questionnaire, covering socio-demographic characteristics, cervical cancer knowledge, perception, risk factors, and preventive practices. Chi-square tests and descriptive statistics were utilized for data analysis.Results: The study revealed a predominant presence of adolescents, with more than half aged 25 or younger. While general knowledge levels varied, a significant proportion exhibited accurate knowledge about cervical cancer, emphasizing the importance of pap smear tests and early detection. Positive perceptions were prevalent, especially among single individuals. Risk factors such as early sexual debut and multiple partners were notable concerns, underlining the vulnerability of this demographic.Conclusion: Accurate knowledge and perceptions are pivotal in shaping preventive practices. The study underscores the urgency for targeted educational initiatives, dispelling misconceptions, and promoting early detection methods like pap smear tests. Collaborative efforts involving healthcare providers, educational institutions, and policymakers are vital in combating cervical cancer among university students.Recommendations: Tailored interventions focusing on accurate information dissemination, emphasizing early detection methods, should be implemented within university campuses. Mass media campaigns and educational programs can significantly enhance awareness. Collaborative efforts should be fostered between healthcare providers, educational institutions, and policymakers to ensure effective cervical cancer prevention strategies.